Exploring the relationships between local agrifood system resilience, multiple measures of development, and health in the Southern United States. Issue 2 (15th March 2019) - Green, John J.; Worstell, Jim; Canarios, Caroline; Haggard, Rachel; Alford, Katrina; Bush, Sydney
ABSTRACT: Resilience has become an increasingly popular concept, with numerous frameworks to address a range of topics. Among other approaches, constructing domain-specific measures focused on the local level provides opportunities to explore the relationships between resilience and development concerns like inequality, poverty, health, and efforts to improve wellbeing. Informed by livelihoods, community capitals, and resilience literature, and using publicly available county-level data, this article explores the associations between agrifood system indicators, broader socioeconomic development, and health in the Southern US. Of interest are the associations between socioeconomic status, social capital, agrifood system resilience, traditional food desert measures, and population health outcomes of self-rated health and premature age-adjusted mortality. Regression analysis demonstrates that local agrifood system resilience is associated with population health. This study helps scholars, practitioners, and policy analysts to have a more nuanced understanding of the ways development of local agrifood systems intersect with broader community development goals.